1992
DOI: 10.1021/bc00014a005
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships in indium-111 radioimmunoconjugates

Abstract: Conjugates formed by reaction of monoclonal antibody B72.3 with benzyl isothiocyanate derivatives of four amino polycarboxylate chelators (NTA, EGTA, EDTA, DTPA) were labeled with indium-111 and administered iv to athymic mice bearing antigen-positive (LS174T) and antigen-negative (A375) human tumor xenografts. Conjugate immunoreactivities, antibody dose, and xenograft size were controlled, so that the effects of varying chelate structure could be evaluated under conditions where immunological and physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…56 Surprisingly, despite the exceptional mouse serum stability of [In(decapa)] 2− , the in vivo stability in mice was found to be suboptimal, with slower clearance from the blood pool and most notably high persistent kidney (3.68 ± 0.54% ID/g) and increasing bone uptake (1.95 ± 0.12% ID/g) over 24 h; however, all other organs contained less than 1% ID/g after 24 h (Figure 4, Table 3). Although these values are inadequate when compared to the in vivo stability and clearance of exceptionally stable chelators like [ 111 In(DOTA)] − and [In(octapa)] − , it is still fair when compared to the very unstable 111 In-citrate complex, which has shown values of 18.7 ± 3.7% ID/g in the kidneys after 24 h. 57 Often 111 InCl 3 and 111 In-citrate are used to emulate the conditions of an unstable chelator that would undergo complete and rapid decomposition/transchelation in vivo. One commonly cited study (Ando et al) has shown 111 InCl 3 to have higher liver, spleen, and kidney uptake than 111 Incitrate; 56 however, another study has shown the kidney uptake of 111 InCl 3 at 24 h in healthy rats to be 2.58 ± 0.83% ID/g, 58 which is significantly less than the value for 111 In-citrate cited above of 18.7 ± 3.7% ID/g, 57 and contradicts the observations from Ando et al 56 Additionally, the highly anionic 111 In-citrate clears much more quickly through the kidneys than 111 InCl 3 , demonstrating that the hypothesis of rapid and complete dissociation upon introduction of these radiometal species into an animal is not accurate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Surprisingly, despite the exceptional mouse serum stability of [In(decapa)] 2− , the in vivo stability in mice was found to be suboptimal, with slower clearance from the blood pool and most notably high persistent kidney (3.68 ± 0.54% ID/g) and increasing bone uptake (1.95 ± 0.12% ID/g) over 24 h; however, all other organs contained less than 1% ID/g after 24 h (Figure 4, Table 3). Although these values are inadequate when compared to the in vivo stability and clearance of exceptionally stable chelators like [ 111 In(DOTA)] − and [In(octapa)] − , it is still fair when compared to the very unstable 111 In-citrate complex, which has shown values of 18.7 ± 3.7% ID/g in the kidneys after 24 h. 57 Often 111 InCl 3 and 111 In-citrate are used to emulate the conditions of an unstable chelator that would undergo complete and rapid decomposition/transchelation in vivo. One commonly cited study (Ando et al) has shown 111 InCl 3 to have higher liver, spleen, and kidney uptake than 111 Incitrate; 56 however, another study has shown the kidney uptake of 111 InCl 3 at 24 h in healthy rats to be 2.58 ± 0.83% ID/g, 58 which is significantly less than the value for 111 In-citrate cited above of 18.7 ± 3.7% ID/g, 57 and contradicts the observations from Ando et al 56 Additionally, the highly anionic 111 In-citrate clears much more quickly through the kidneys than 111 InCl 3 , demonstrating that the hypothesis of rapid and complete dissociation upon introduction of these radiometal species into an animal is not accurate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although these values are inadequate when compared to the in vivo stability and clearance of exceptionally stable chelators like [ 111 In(DOTA)] − and [In(octapa)] − , it is still fair when compared to the very unstable 111 In-citrate complex, which has shown values of 18.7 ± 3.7% ID/g in the kidneys after 24 h. 57 Often 111 InCl 3 and 111 In-citrate are used to emulate the conditions of an unstable chelator that would undergo complete and rapid decomposition/transchelation in vivo. One commonly cited study (Ando et al) has shown 111 InCl 3 to have higher liver, spleen, and kidney uptake than 111 Incitrate; 56 however, another study has shown the kidney uptake of 111 InCl 3 at 24 h in healthy rats to be 2.58 ± 0.83% ID/g, 58 which is significantly less than the value for 111 In-citrate cited above of 18.7 ± 3.7% ID/g, 57 and contradicts the observations from Ando et al 56 Additionally, the highly anionic 111 In-citrate clears much more quickly through the kidneys than 111 InCl 3 , demonstrating that the hypothesis of rapid and complete dissociation upon introduction of these radiometal species into an animal is not accurate. 56 Considering these inconsistencies, it is important to utilize internal standards (such as [ 111 In-(DOTA)] − in this study), and additionally there is a need for more clear and reliable baseline data for the biodistribution of 111 In in its most commonly used forms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several other modifications of these BCAs have been investigated to improve labeling efficiency and in vivo stability. [5][6][7][8] When internalized by cells, these proteins undergo intracellular catabolism with subsequent formation of radiolabeled metabolites. In particular, after endocytotic internalization, the ligand is delivered to the endosome and then to the lysosome.…”
Section: Introductionmentioning
confidence: 99%
“…For studies involving macromolecules such as antibodies, biologically active proteins, polymers, and their drug conjugates, residualizing radiolabels have been developed to trace their tissue distribution. So far, hydrophilic bifunctional chelate-radioactive metal complexes or radioiodination using sugar-containing spacers has been used as residualizing radiolabels for such compounds ( ). In these approaches, relatively large, hydrophilic molecules are incorporated into the structure of the radiolabeled adducts.…”
Section: Introductionmentioning
confidence: 99%